Reprogramming of H3K27me3 Is Critical for Acquisition of Pluripotency from Cultured Arabidopsis Tissues - He, Chongsheng (Public Library of Science, 2012)
In plants, multiple detached tissues are capable of forming a pluripotent cell mass, termed callus, when cultured on media containing appropriate plant hormones. Recent studies demonstrated that callus resembles the root-tip meristem, even if it is derived from aerial organs. This finding improves our understanding of the regeneration process of plant cells; however, the molecular mechanism that guides cells of different tissue types to form a callus still remains elusive. Here, we show that genome-wide reprogramming of histone H3 lysine 27 trimethylation (H3K27me3) is a critical step in the leaf-to-callus transition. The Polycomb Repressive Complex 2 (PRC2) is known to function in establishing H3K27me3. By analyzing callus formation of mutants corresponding to different histone modification pathways, we found that leaf blades and/or cotyledons of the PRC2 mutants curly leaf swinger (clf swn) and embryonic flower2 (emf2) were defective in callus formation. We identified the H3K27me3-covered loci in leaves and calli by a ChIP–chip assay, and we found that in the callus H3K27me3 levels decreased first at certain auxin-pathway genes. The levels were then increased at specific leaf genes but decreased at a number of root-regulatory genes. Changes in H3K27me3 levels were negatively correlated with expression levels of the corresponding genes. One possible role of PRC2-mediated H3K27me3 in the leaf-to-callus transition might relate to elimination of leaf features by silencing leaf-regulatory genes, as most leaf-preferentially expressed regulatory genes could not be silenced in the leaf explants of clf swn. In contrast to the leaf explants, the root explants of both clf swn and emf2 formed calli normally, possibly because the root-to-callus transition bypasses the leaf gene silencing process. Furthermore, our data show that PRC2-mediated H3K27me3 and H3K27 demethylation act in parallel in the reprogramming of H3K27me3 during the leaf-to-callus transition, suggesting a general mechanism for cell fate transition in plants.